The Influence of the Effectiveness of Visual Learning Media on Economic Learning Outcomes across Interests of Class X Students at SMAN 1 Kampar Kiri - Nur Izati; Gani Haryana; Mujiono Mujiono (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the effect of the effectiveness of visual learning media on economic learning outcomes across interests of class X students at SMAN 1 Kampar Kiri. The method used in this study is a correlational method with a quantitative approach. The sample used in the study was 73 people. The data collection method used in this study used questionnaires and tests, test instruments to determine learning outcomes and questionnaires to determine student responses to the use of visual power point media. The analytical techniques used were descriptive analysis, classical assumption tests and simple linear regression. The research results obtained showed that the effectiveness of visual learning media had a positive and significant effect on student learning outcomes with the regression equation Y = 4,272 + 0.813 (X)X1 + e and contributed 48% and the rest was influenced by other factors not examined.